A Humanistic-Ecological Project-Based Learning Model Integrating Balinese Local Wisdom for Adolescent Development in Bali’s Tourism Contexts: A Systematic Literature Review - Bestari, Ida Ayu Purnama; Tika, I Nyoman; Atmadja, Anantawikrama Tungga; Suastra, I Wayan (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This systematic literature review synthesizes evidence on Project-Based Learning (PjBL) integrated with Balinese local wisdom for adolescent human resource development in Bali’s tourism contexts. Following PRISMA 2020 guidelines, a Scopus search (2016-2025) identified 21 empirical studies. Each was coded for PjBL implementation, local wisdom integration, humanistic/ecological perspectives, youth development, and tourism relevance. Findings show widespread integration of humanistic/ecological perspectives and local wisdom. However, explicit PjBL implementation appeared in only 8 of 21 studies (38.1%), with others showing project-like elements. Recurring limitations include partial local wisdom integration and limited attention to ecological impact and youth agency. Based on this, the study proposes a seven-stage PjBL syntax operationalizing Tri Hita Karana, Tat Twam Asi, and menyama braya. This model offers a culturally grounded framework for adolescent HRD, addressing existing gaps and promoting humanistic-ecological sustainability in Bali's unique tourism setting.